Pengaruh Resiko Pembiayaan Dan Resiko Likuiditas Terhadap Efektifitas Laba Dimediasi Kecukupan Modal Di Perbankan Syariah - Yudi Siyamto; Yuwita Ariessa Pravasanti (ITB AAS INDONESIA, 2024)
This study aims to analyze the impact of liquidity risk and financing risk on profit effectiveness, with capital adequacy as a mediating variable, in Indonesian Islamic banks. The data used in this study consists of monthly data published by the Financial Services Authority (OJK) in the form of Islamic banking statistics from June 2014 to December 2023. The analytical method employed is Partial Least Squares-Structural Equation Modeling (PLS-SEM) using SmartPLS. The results show that both liquidity risk and financing risk have a significant negative impact on profit effectiveness. Additionally, capital adequacy is proven to significantly mediate the relationship between these risks and profit effectiveness. Further analysis reveals that capital adequacy has a significant positive direct effect on profit effectiveness, indicating that Islamic banks with adequate capital are better positioned to manage risks and generate optimal profits. The novelty of this research lies in identifying the mediating role of capital adequacy in the context of Islamic banking, which has previously received limited attention in the literature. These findings have important implications for risk management in Islamic banking, emphasizing the importance of maintaining adequate capital to support stable and sustainable financial performance.